Дискуссия как одно из средств стимулирования и регулирования коммуникативной деятельности на занятиях иностранного - Жакебаева, М.Г. (My University, 2016)
This article reviews the problem of communicative competence using group activities one of which is discussion while studying the second foreign language. Discussion demands the skills to generalize, express own opinion to the facts and give arguments concerning students point of view.
Keywords: independent work; communicative competence; linguistique competence; control of individual and group work